Real-Time Speed Control of a Mobile Robot Using PID Controller - MohandSaidi, Sabrina; Mellah, Rabah (University of Eloued جامعة الوادي, 2022)
This paper presents PID control of speed implemented by PC on a unicycle mobile robot. The designed control has been applied to a nonholonomic mobile robot dr Robot i90. The results obtained from the experiment show the efficiency of this strategy control, even in the case where we introduce a disturbance for the system such as for example putting an overload for the robot
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Real-time speed control, Non-holonomic mobile robot, PID Controller